Acceptance and Use of Internet Banking: A Digital Divide Perspective - Gorbacheva, Elena; Niehaves, Björn; Plattfaut, Ralf; Becker, Jörg (19th European Conference on Information Systems (ECIS), 2011)
Internet banking offers major advantages for both banks and their customers. However, not all people have equal access or skills to use such services. As banks are interested in migrating customers online, they need to reveal the conditions of internet banking services acceptance and use. The main objective of this study is to understand the factors influencing internet banking adoption taking into account insights from the digital divide theory. In order to explain internet banking usage we developed a research model drawing from the Unified Theory of Acceptance and Use of Technology (UTAUT) and Digital Divide research. Moreover, a qualitative pre-study has led to the creation of a new construct: perceived security. The model was tested against comprehensive survey data (n = 503). As a result, more than 90 percent of the variance of internet banking usage was explained by the elaborated model. Results demonstrate that the strongest factor influencing the intention to adopt internet banking services is the degree to which an individual believes that it is safe to use such services. Hence, this paper contributes to existing technology acceptance literature by introducing the construct of perceived security. Other major implications for theory and practice are discussed.
Keywords: Digital Divide; Internet Banking; Quantitative Study; UTAUT